Managers' perception and attitude toward financial risks associated with SMEs: Analytic hierarchy process approach - Mahmaod Alrawad; Abdalwali Lutfi; Mohammed Amin Almaiah; Adi Alsyouf; Akif Lutfi Al-Khasawneh; Hussin Mostafa Arafa; Nazar Ali Ahmed; Ahmad M. AboAlkhair; Magdy Tork (Journal of Risk and Financial Management, 2023)
This study aimed to identify financial and cash flow risks associated with SMEs and investigated how managers perceived these risks using the analytical hierarchical process (AHP). Accordingly, a three-level decision model was structured using two criteria, probability and consequences, and a list of six different types of risks as decision alternatives. Data were collected by a survey questionnaire from SME managers/owners and analyzed in accordance with the AHP method. The results show that the priority weight for risk criteria was 52% for probability and 48% for consequences. Further, with an average weight of 18.8%, the risk of an increase in bank charges ranked as the highest type of risk faced by SMEs. However, the risk of low or no profits was ranked as the lowest with an average weight of 13.4%. This study is one of the few, if not the first, to investigate SME managers' perceptions using an AHP method and to provide insightful information on how SME managers/owners perceived various financial and cash flow risks. The study results may support the use of the AHP method in understanding managers' perceptions and attitudes toward various types of risks associated with SMEs.
Keywords: 650; analytic hierarchy process; SME; risk assessment; cash flow; financial risks